Relation between brain temperature and white matter damage in subacute carbon monoxide poisoning - Fujiwara, Shunrou (Sci Rep, 2016)
In the previous studies, carbon monoxide (CO) poisoning showed an imbalance between cerebral perfusion and metabolism in the acute phase and the brain temperature (BT) in these patients remained abnormally high from the acute to the subacute phase. As observed in chronic ischemic patients, BT can continuously remain high depending on impairments of cerebral blood flow and metabolism; this is because heat removal and production system in the brain may mainly be maintained by the balance of these two factors; thus, cerebral white matter damage (WMD) affecting normal metabolism may affect the BT in patients with CO poisoning. Here, we investigated whether the BT correlates with the degree of WMD in patients with subacute CO-poisoning. In 16 patients with subacute CO-poisoning, the BT and degree of WMD were quantitatively measured by using magnetic resonance spectroscopy and the fractional anisotropy (FA) value from diffusion tensor imaging dataset. Consequently, the BT significantly correlated with the degree of WMD. In particular, BT observed in patients with delayed neuropsychiatric sequelae, a crucial symptom with sudden-onset in the chronic phase after CO exposure, might indicate cerebral hypo-metabolism and abnormal hemodynamics like “matched perfusion,” in which the reduced perfusion matches the reduced metabolism.